Cohort study to determine the risk of pressure ulcers and developing a care bundle within a paediatric intensive care unit setting. (August 2019) - Smith, Hazel A.; Moore, Zena; Tan, Mong Hoi
Abstract: Objective: Determine the incidence and risk factors for pressure ulcers in a paediatric intensive care unit. Use the information gathered to develop preventive pressure ulcer care bundles. Research methodology: Prospective cohort study using Braden Q Scale for Predicting Pressure Sore Risk and European Pressure Ulcer Advisory Panel Pressure Ulcer Staging tool. Setting: General paediatric intensive care unit in a tertiary level hospital between May and October 2017. Results: Seventy-seven children were recruited. Most children were male (n = 42, 54.5%) and all nine children (11.7%) that developed a pressure ulcer were male. The main risk factor for developing a pressure ulcer was lack of physical activity. None of the children assessed as high or severe risk developed a pressure ulcer. Eight (89%) pressure ulcers were assessed as grade one. Seven pressure ulcers (77.8%) were on the facial and scalp area and all seven children were receiving airway support at the time the pressure ulcers developed. Conclusion: Incidence of pressure ulcers was 11.7%, with the facial and scalp area the most common anatomical areas affected. Medical devices appeared to be the prime causative factor. Based on our data we have modified and launched the SSKIN care bundle for the paediatric intensive care unit setting.